2019
DOI: 10.15789/1563-0625-2019-3-527-538
|View full text |Cite
|
Sign up to set email alerts
|

Determining Reference Ranges for Trec and Krec Assays in Immune Deficiency Screening of Newborns in Russian Federation

Abstract: In this work, we used a reference population of newborns and sampled dried blood spots on Guthrie cards of 2,739 individual samples to determine the reference intervals for TRECs and KRECs values, in order to diagnose primary immunodeficiency by means of neonatal screening. The median absolute values for TRECs and KRECs were 195 (CI95%: 185-206) and 185 (CI95%: 176-197) copies per μl, respectively; the normalized value for TRECs was 2780 (CI95%: 2690-2840), and for KRECs, 2790 (CI95%: 2700-2900) copies per 2 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Patients in the acute stage of COVID-19 and COVID-19 survivors demonstrate specific alterations in circulating immune cell subsets [ 1 , 5 , 10 , 12 ]. The analysis of TREC and KREC levels characterized the functional activity of central organs of the immune system and, therefore, the release of naïve T and B cells into peripheral blood [ 13 , 14 , 16 ]. Previous studies demonstrated the clinical significance of TREC and KREC concentrations in the prognosis of COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients in the acute stage of COVID-19 and COVID-19 survivors demonstrate specific alterations in circulating immune cell subsets [ 1 , 5 , 10 , 12 ]. The analysis of TREC and KREC levels characterized the functional activity of central organs of the immune system and, therefore, the release of naïve T and B cells into peripheral blood [ 13 , 14 , 16 ]. Previous studies demonstrated the clinical significance of TREC and KREC concentrations in the prognosis of COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…The normalized TREC and KREC values were estimated for 10 5 leukocytes, taking into account the serum albumin (ALB)-based internal control by the method suggested by M.A. Gordukova et al (2019) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations